BDNF, sHLA-G, and sTREM-1 are useful blood biomarkers for identifying grade IV glioma patients - Kluckova, Kristina; Kozak, Jan; Svajdler, Marian; Steno, Juraj; Matejcik, Viktor; Durmanova, Vladimira; Zsemlye, Eszter; Bucova, Maria (Neoplasma, 2023)
Inflammation and immunity belong to the main factors influencing tumor growth. In this study, we attempted to identify a profile of biomarkers associated with gliomas. We found decreased serum levels of sTREM-1 (soluble triggering receptor expressed on myelocytes) and increased levels of IL-10 in all grades of glioma patients in comparison with healthy controls (sTREM-1: grade II: p=0.0051, grade III: p=0.02, grade IV: p=0.01; IL-10: grade II: p=0.0017, grade III: p=0.03, grade IV: p=0.007). However, we did not find any combination of tested markers with good sensitivity and specificity in grades II and III of glioma patients to discriminate them from healthy controls. In grade IV glioma patients, two sets of markers showed promising results in distinguishing patients from healthy people. For the first set consisting of four selected markers, sTREM-1, sHLA-G, BDNF, and IL-13, the ROC curves indicate a good discriminatory capability for glioblastoma patients (AUC=0.9510). The best discriminatory capability for glioblastoma patients (AUC=0.9534) was found for the second set consisting of three selected markers sTREM-1, sHLA-G, and BDNF with 79.2% sensitivity and 94.1% specificity.
Keywords: Glioma; interleukin-10; Humans; Glioblastoma; Biomarkers; receptor TREM-1; mozkový neurotrofický faktor; Triggering Receptor Expressed on Myeloid Cells-1; Brain-Derived Neurotrophic Factor; biologické markery; Interleukin-10; glioblastom; gliom; lidé